Hydraulic Carica as A Local Commodity Potential Based Natural Scientific Instrument - Firdaus Firdaus; Pamungkas Stiya Mulyani (Indonesian Journal of Science and Education (IJOSE), 2018)
This research aimed to develop a local commodity potential based natural, scientific instrument called Hydraulic Carica (Hydrocar). It belonged to research and development studies. The instrument was developed through several stages: information acquisition, planning, development, validation and limited testing. It was validated by experts, practitioners and students during the limited testing stage. The product of research was a natural, scientific instrument based on local potential commodity in Wonosobo regency called Hydrocar (Hydraulic Carica). The instrument was developed according to the criteria with ”very good” scores on media, material and method aspects. Hydrocar is a suitable media for natural, sciences learning because it overcomes time and space limitation, improves students’ motivation and understanding and allows them to be more actively engaged in classroom. Keywords: Hydraulic Carica, Natural Scientific Instrument, Local Commodity Potential.